HEALTH CHECKING OF BLOOD PRESSURE AND RANDOM BLOOD GLUCOSE IN AREA OF TANJUNG PINANG IN PALANGKA RAYA - Istiningsih, Titik; Wahyuni, Seri (Jurnal Abdimas ITEKES, 2022)
ABSTRACTEnglish translation. Degenerative disease is a disease caused by decreased of the body organ function. Some degenerative diseases are Hypertension, Coronary Heart, Diabetes Mellitus, Gout, etc. Many things become the cause of growing degenerative diseases, they are: unhealthy lifestyles such as smoking, lack of exercise and stress. The trend of degenerative diseases is increasing day by day. Currently, there was the changing of incidence number in the degenerative diseases, the disease was originally experienced by the elderly aged over 50 years old. Currently, degenerative diseases could be found at the age of 30-40 years old. (BPJS, 2016). The prevalence of hypertension in Indonesia was 25.8%, while the prevalence of diabetes mellitus was 6.9%. The prevalence of hypertension and diabetes mellitus is expected to continue to increase. The prevalence of hypertension is predicted to increase 60% in 2025, which is about 1.56 million people, while the prevalence of diabetes mellitus is estimated to reach 21.3 million people in 2030. (Riskesdas, 2013). Prevention of degenerative diseases can be prevented by health screening at over 30 years old. Most people with hypertension and diabetes mellitus have no complaints, so the only way to detect them is to do the blood pressure and blood sugar level screening. A person can be known early that he or she suffers from hypertension or diabetes mellitus, so that prevention efforts can be made in order to the progressivity of hypertension and diabetes mellitus does not continue until it causes disability or death (Kemenkes RI, 2012). The long-term plan of this program is all people aged over 30 years old are screened in Tanjung Pinang village, Pahandut district, Palangka Raya city, Central Kalimantan province, exposed to the information about the importance of early screening of Hypertension and Diabetes Mellitus and given a solution by recommending regular medical check-up every 6 months. The result of program can be published in local and national media. Keywords: Screening, Hypertension, Diabetes Mellitus